DO POLITICAL CONNECTIONS MODERATE GOVERNANCE EFFECTS ON FIRM VALUE? - Heriadi, Wales; Kamaliah, Kamaliah; Oktari, Vera (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines whether political connections strengthen or substitute for effective corporate governance in enhancing firm value, drawing on agency theory, legitimacy theory, and political economy perspectives. The sample consists of 215 firm-year observations from mining companies listed on the Indonesia Stock Exchange during 2020–2024. The governance mechanisms analyzed include independent commissioners, board size, audit committees, institutional ownership, and managerial ownership, with political connections tested as a moderating variable. Using panel regression and moderated regression analysis, the results show that independent commissioners and board size have a significant positive effect on firm value, while CSR disclosure, institutional ownership, managerial ownership, and audit committees are not significant. Political connections also fail to moderate the relationship between governance mechanisms or CSR and firm value. The model demonstrates moderate explanatory power, indicating that internal governance explains a meaningful proportion of firm value variation. These findings challenge the political economy argument that political ties enhance firm value and reinforce the primacy of internal governance mechanisms. The study extends the literature on governance and political connections in emerging markets, particularly in highly regulated industries.